2005
DOI: 10.1210/en.2004-0709
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Modulates Thymocyte Development in Vivo through a Combined Action of Laminin and CXC Chemokine Ligand 12

Abstract: Previous evidence indicates that GH modulates thymic cell migration. In this study we approached this issue in vivo, studying thymocyte migration in GH transgenic animals and in normal mice treated intrathymically with GH. Extracellular matrix and chemokines are involved in thymocyte migration. In this respect, thymocyte adhesion to laminin was higher in GH-treated animals than controls, and the numbers of migrating cells in laminin-coated Transwells was higher in GH-transgenic and GH-injected mice. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 31 publications
6
83
0
Order By: Relevance
“…This was seen in both C57/BL6 and NOD thymocytes. Interestingly, it has also been reported in growth hormone transgenic mice, as well as in BALB/c mice infected with the protozoan parasite Trypanosoma cruzi, the causative agent of Chagas' disease (16,17).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This was seen in both C57/BL6 and NOD thymocytes. Interestingly, it has also been reported in growth hormone transgenic mice, as well as in BALB/c mice infected with the protozoan parasite Trypanosoma cruzi, the causative agent of Chagas' disease (16,17).…”
Section: Discussionmentioning
confidence: 90%
“…Cells were washed and maintained in PBS-5% FCS for cell counting and subsequently submitted to four-or six-color immunofluorescence staining as previously described (16). Cells were then evaluated by flow cytometry in a FACSCalibur or FACSCanto II device (BD Biosciences).…”
Section: Cytofluorometrymentioning
confidence: 99%
“…Some reports indicate a role for GH as an immune response activator (5,20); we thus characterized immune cell populations in blood, spleen, and peripheral lymph nodes of NOD and NOD-Tg bGH mice. Flow cytometry analysis showed similar immune cell populations in both mouse lines (Table S1).…”
Section: Nod-tg Bgh Mice Have Normal Delayed Type Hypersensitivitymentioning
confidence: 99%
“…GH/IGF-1 could act on numerous thymic functions. Different studies on rodents have shown that the somatotrope axis act on thymocyte number [83,84], on TEC growth [85,86] and on the production by TEC of the chemokines CXCL12 and CCL25 [87,88].…”
Section: The Somatotrope Gh/igf-1 Axis and Thymus Function In Rodentsmentioning
confidence: 99%
“…As for HAARTtreated HIV infection, conjonction of thymotropism of pathogen, GH/IGF-1 axis disturbance and correlated effects on T immune system suggest that GH can be considered as an immunomodulating substance for boosting the T-cell system and controlling parasite replication, and a combination of GH with anti-infectious drugs could be a new therapeutic strategy to reduce the harmful effects of Chagas disease. However, it should be noted that GH increases CXCL12 expression and pre-T cell migration [88], one of the chemokine augmented after T. cruzi infection with proposed negative consequences. Therefore, cautions must be taken before to concluding that GH treatment would always increment the benefit-cost ratio.…”
Section: Implications For Chagas Diseasementioning
confidence: 99%